Adoption of e-health services from the user's perspective: Identification of the relevant determinants of adoption to benefit from the promises - Manfred Bruhn; Isabel Schmidt (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2010)
The purpose of this paper is to construct a conceptual framework for the adoption decision of potential users in the field of electronic health services including the relevant determinants, sources of information aimed at reducing uncertainty about the innovation and the barriers that inhibit the adoption. So far, adoption research has widely ignored the healthcare sector. Consequently, no comprehensive studies on adoption decision processes yet exist. Using a semi-structured field manual, we interviewed 15 experts from the business, academic and public health sector. In addition to its comprehensiveness, our study specially highlights the particularities of this process that are associated with health services, the involvement of multiple decision-makers, and the ambivalent role presented by the attending physician (where present).
Keywords: 330; electronic health services; adoption process; determinants of adoption; barriers of adoption